Culture and Deaf Women's Body Image. (12th September 2018) - Aldalur, Aileen; Schooler, Deborah
Abstract: The sociocultural model of eating disorders highlights the role of internalization of the thin ideal in the development of negative body image and disordered eating. Considering the limited diversity of models in mainstream media, individuals belonging to minoritized cultural groups may resist identifying with and internalizing mainstream beauty messages. The extent of internalization may also depend on an individual's acculturation status and experiences of acculturative stress. This study applied the sociocultural model to culturally Deaf women. Data were collected from 96 deaf, female, undergraduate students. Results support the sociocultural model; higher rates of internalization were associated with negative body image and disordered eating behaviors. However, neither Deaf nor Hearing acculturation predicted internalization. Despite this finding, stronger acculturation with either Deaf or Hearing culture predicted more positive body image, and higher rates of acculturative stress predicted negative body image and disordered eating behaviors. Implications for clinical practice are discussed.